Heart rate variability for early detection of cardiac iron deposition in patients with transfusion-dependent thalassemia - Suchaya Silvilairat (2018)
© 2016 Silvilairat et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background: Iron overload cardiomyopathy remains the major cause of death in patients with transfusion-dependent thalassemia. Cardiac T2∗ magnetic resonance imaging is costly yet effective in detecting cardiac iron accumulation in the heart. Heart rate variability (HRV) has been used to evaluate cardiac autonomic function and is depressed in cases of thalassemia. We evaluated whether HRV could be used as an indicator for early identification of cardiac iron deposition. Methods: One hundred and one patients with transfusion-dependent thalassemia were enrolled in this study. The correlation between recorded HRV and hemoglobin, non-transferrin bound iron (NTBI), serum ferritin and cardiac T2∗ were evaluated. Results: The median age was 18 years (range 8-59 years). The patient group with a 5-year mean serum ferritin >5,000 ng/mL included significantly more homozygous β-thalassemia and splenectomized patients, had lower hemoglobin levels, and had more cardiac iron deposit than all other groups. Anemia strongly influenced all domains of HRV. After adjusting for anemia, neither serum ferritin nor NTBI impacted the HRV. However cardiac T2∗ was an independent predictor of HRV, even after adjusting for anemia. For receiver operative characteristic (ROC) curve analysis of cardiac T2∗ ≤20 ms, only mean ferritin in the last 12 months and the average of the standard deviation of all R-R intervals for all five-minute segments in the 24-hour recording were predictors for cardiac T2∗ ≤20 ms, with area under the ROC curve of 0.961 (p<0.0001) and 0.701 (p = 0.05), respectively. Conclusions: Hemoglobin and cardiac T2∗ as significant predictors for HRV indicate that anemia and cardiac iron deposition result in cardiac autonomic imbalance. The mean ferritin in the last 12 months could be useful as the best indicator for further evaluation of cardiac risk. The ability of serum ferritin to predict cardiac risk is stronger than observed in other thalassemia cohorts. HRV might be a stronger predictor of cardiac iron in study populations with lower somatic iron burdens and greater prevalence of cardiac iron deposition.